Primary School Teachers' Material Usage Concerning Three-Dimensional Work at Visual Arts Course (Soap Sculpture Example) - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2016)
In this research it is aimed to determine primary school teachers' (n=143) views with respect to the material usage of three-dimensional works in visual arts lesson. The unrefined data acquired by the statements of the participants is analysed with qualitative analysis techniques and also frequency, percentage analyses are performed. By this way techniques used by primary school teachers in Visual Arts course, to which works (two or three-dimensional work) they gave more importance, from which works (two or three-dimensional work) they took more efficiency, which of the three-dimensional works they preferred, which materials and techniques they used in three-dimensional works, for what reason they made these works and which materials they preferred to use while making sculpture work were determined. With open-ended questions in the questionnaire, it was aimed to put forward teachers' views on three-dimensional studies. According to findings from the study, Primary school teachers use two-dimensional works more often three-dimensional works (f=140, %=97,9), They opt for mask making the most regarding three-dimensional works (f=50, %=39,4), They use play dough during their three-dimensional works (f=101, %=38,8), They perform threedimensional works aiming at developing handcraft skills (f=110, %=33,4) and in sculpture performing they use waste material (f=28, %=30,1) the most. The reasons why primary teachers do not use threedimensional works in Visual Arts course can be summarized as follows: unfavourable environment, the teachers lack of knowledge, material access problems, economic reasons, the lack of time, inadmissibility to the level (age), crowded classes, failure to see the material secure, the lack of family support, hygiene problem, seeing the course insignificant and lack of resources.
Keywords: Visual arts; three-dimensional works; material; sculpture; primary school teachers